Doctrine of Trinity Based on Qur’anic and Biblical Studies - Ahmad Hermawan (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2018)
This paper will discuss the problem of Trinity as a doctrine that underlies the faith of ‎Christianity. It is considered as a delusion theological doctrine which is both ambiguous and ‎compelled. Al-Qur’an criticizes the confusion of Trinity as a doctrinal astray of human ‎invention possessing no basis from Allah and it has triggered major conflicts within the ‎Christianity itself. The confusion of Trinity willl be revealed through the method on historical criticism based on Qur’anic and Biblical Studies the ‎confusion of Trinity is revealed. There are at least two aspects of the fallacy possessed by ‎Trinity: Political aspect and the abberation of Christianity religious teachings. Moreover, there ‎is an identical proof regarding the political interests of the Roman Emperor Constantine ‎influencing the formulation of Trinity at Nicaea Council 325 C.E. The influence was an ‎invasion of polytheism and paganism into Trinity confusing the elements of monotheism and ‎polytheism. The distortion of religious teachings in Trinity is the presence of teachings of Jesus ‎Christ  concerning an obligation to worship hm as God, while it does not exist in Gospel. The ‎doctrine of Jesus divinity came from Paul. It precisely deviated monotheism principle. ‎Consequently, there was a conflict in Christianity schools in respect to Trinity since that era up ‎to the present day.‎